Interaction between Rice stripe virus Disease- Specific Protein and Host PsbP Enhances Virus Symptoms - Kong, Lingfang; Wu, Jianxiang; Lu, Lina; Xu, Yi; Zhou, Xueping (Molecular plant, 2014)
Rice stripe virus （RSV） causes severe diseases in Oryza sativa （rice） in many Eastern Asian countries. Diseasespecific protein （SP） of RSV is a non-structural protein and its accumulation level in rice plant was shown to determine the severity of RSV symptoms. Here, we present evidence that expression of RSV SP alone in rice or Nicotiana benthamiana did not produce visible symptoms. Expression of SP in these two plants, however, enhanced RSV- or Potato virus X （PVX）- induced symptoms. Through yeast two-hybrid screening, GST pull-down, and bimolecular fluorescence complementation assays, we demonstrated that RSV SP interacted with PsbP, a 23-kDa oxygen-evolving complex protein, in both rice and N. benthamiana. Furthermore, our investigation showed that silencing of PsbP expression in both plants increased disease symptom severity and virus accumulation. Confocal microscopy using N, benthamiana protoplast showed that PsbP accu- mulated predominantly in chloroplast in wild-type N. benthamiana cells. In the presence of RSV SP, most PsbP was recruited into cytoplasm of the assayed cells. In addition, accumulation of SP during RSV infection resulted in alterations of chloroplast structure and function. Our findings shed light on the molecular mechanism underlying RSV disease symptom development.